(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to the relationship between a lack of motivation for distance learning and an excessive psychological entitlement among university students during e-learning in light of the Corona pandemic. The current research is limited to the students of the Colleges of Education for Human Sciences and the College of Education for Pure Sciences from the academic year (2020-2021) and for the morning study only. To achieve the objectives of the research, a random sample of (200) male and female students was selected, with (150) male and female students from the College of Education for Human Sciences and (50) male and female students from the College of Education for Pure Sciences. To achieve the objectives of the research, the researcher built two tools, one to measure the lack of motivation for distance learning, consisting of (22) items, and the second to measure psychological over-entitlement, consisting of (20) items, and three alternatives were placed in front of each paragraph, which are (always apply to me, sometimes apply to me, Not applicable to me) Grades were given (3, 2, 1) respectively. The researcher verified the validity of the two tools by the method of apparent validity and construct validity, and verified their stability using the re-test method and the Alpha-Kronback method. The researcher used the following statistical methods: chi-square (Ka2), t-test for two independent samples, t-test for one sample, and Pearson correlation coefficient. The research reached the following results: 1_ University students have a lack of motivation for distance learning during e-learning in light of the Corona pandemic. 2_ University students have excessive psychological entitlement during e-learning in light of the Corona pandemic. 3_ There is a direct relationship between lack of motivation for distance learning and excessive psychological entitlement during e-learning under the Corona pandemic.